An Empirical Study of Mutual Fund Performance and Its Relation with Fund Size - Lu, Daofen (2007)
The increasing popularity of mutual fund investment is a remarkable phenomenon of recent decades. Mutual funds have been among the largest investors and played an important role in the financial market worldwide. The evaluation of mutual fund performance has been achieving a great deal of academic interest since the 1960s. This study employed a time-series data to examine the performance of sixty actively-managed equity growth funds of the United States during the period of July, 2002 to June, 2007. It was based on three fundamental theories of finance and investment, including Modern Portfolio Theory, Capital Asset Pricing Model, and Efficient Market Hypothesis. Three classical performance evaluation models, such as, Treynor's ratio, Sharpe's ratio, and Jensen's Alpha were employed to compare the risk-adjusted returns of sample funds with those of the S&P Composite 1500 index. The result of one-sample t-tests suggests that actively-managed equity growth funds in the United States were able to outperform the market index during the observation period.